Dual Anticancer and Antibacterial Properties of Silica-Based Theranostic Nanomaterials Functionalized with Coumarin343, Folic Acid and a Cytotoxic Organotin(IV) Metallodrug - Maider Ugalde-Arbizu; John Jairo Aguilera-Correa; Victoria García-Almodóvar; Karina Ovejero-Paredes; Diana Díaz-García; Jaime Esteban; Paulina L. Páez; Sanjiv Prashar; Eider San Sebastian; Marco Filice; Santiago Gómez-Ruiz (MDPI AG, 2023)
Five different silica nanoparticles functionalized with vitamin B12, a derivative of coumarin found in green plants and a minimum content of an organotin(IV) fragment (1-MSN-Sn, 2-MSN-Sn, 2-SBA-Sn, 2-FSPm-Sn and 2-FSPs-Sn), were identified as excellent anticancer agents against triple negative breast cancer, one of the most diagnosed and aggressive cancerous tumors, with very poor prognosis. Notably, compound 2-MSN-Sn shows selectivity for cancer cells and excellent luminescent properties detectable by imaging techniques once internalized. The same compound is also able to interact with and nearly eradicate biofilms of Staphylococcus aureus, the most common bacteria isolated from chronic wounds and burns, whose treatment is a clinical challenge. 2-MSN-Sn is efficiently internalized by bacteria in a biofilm state and destroys the latter through reactive oxygen species (ROS) generation. Its internalization by bacteria was also efficiently monitored by fluorescence imaging. Since silica nanoparticles are particularly suitable for oral or topical administration, and considering both its anticancer and antibacterial activity, 2-MSN-Sn represents a new dual-condition theranostic agent, based primarily on natural products or their derivatives and with only a minimum amount of a novel metallodrug.